PROGRAM DEVELOPMENT TO EVALUATE THE GAIT DEVIATION INDEX (GDI) OF CEREBRAL PALSY PATIENTS - Ligarpalupi Paramesti, Alya
Cerebral Palsy (CP) is a non-progressive yet permanent brain condition that leads to various abnormalities affecting movement, balance, posture, muscle tone, and coordination. This research addresses the necessity for an objective and comprehensive assessment to evaluate gait quality in individuals with cerebral palsy. To achieve this goal, a MATLAB-based program was developed to calculate the Gait Deviation Index (GDI) using kinematic parameters obtained from an optical motion capture system. GDI serves as a valuable index capable of distinguishing between normal and abnormal gait patterns in cerebral palsy patients while also providing insight into the severity of their gait deviations. The index combines several essential gait parameters, facilitating a comprehensive understanding of the overall gait quality. By comparing nine kinematic parameters of a subject to normative data, GDI effectively quantifies the deviations in a subject’s gait. The results of this study successfully demonstrate the program's ability to discern between normal and abnormal gait patterns, thus establishing GDI as a promising tool for gait assessment. Health professionals can now leverage GDI to make informed clinical decisions, optimize rehabilitation programs, and assess the efficacy of medical interventions, becoming a valuable asset to enhance patient care and personalized treatment options.